Improving Early Vocabulary Skills with Colorful Visuals: An Evaluation at TK Katolik Santa Maria Tulungagung - Dominika Apri Liya Kristiani; Moh. Hanafi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This study explored the impact of colorful pictures on vocabulary teaching effectiveness for students at TKK Santa Maria Tulungagung. Utilizing a pre-experimental one-group pre-test and post-test design, the research involved TKK Santa Maria Tulungagung students who engaged with colorful pictures. Analysis was conducted using the SPSS 27 statistical program. Findings indicated a significant improvement in vocabulary mastery among students using colorful pictures, with a two-tailed sig. value of 0.006, which is below the 0.05 threshold. The incorporation of colorful pictures not only enhanced understanding but also made the learning process more engaging and enjoyable. Consequently, colorful pictures are deemed an effective strategy for teaching vocabulary to kindergarten students. This research aims to assist teachers in selecting more innovative and efficient methods to enhance vocabulary acquisition at the early childhood education level.